Subcutaneous immunotherapy with aeroallergens - evaluation of adherence in real life - Lourenço, Tatiana (2020)
Introduction. Adherence in allergen immunotherapy is crucial for its efficacy. At least 3 years of treatment are recommended for achieving a long-term modifying effect. Objectives. To assess patient’s adherence and to identify determinant factors for allergen subcutaneous immunotherapy (SCIT) suspension in patients with respiratory allergy. Methods. Retrospective analysis of the medical record of patients submitted to SCIT between January 2013 and December 2016 in our Department. Results. 323 patients were included: 52% female; mean age 30 ± 13 years; average treatment time 19 ± 13 months. 52 patients (16%) stopped SCIT: 54% female; mean age 30 ± 9 years; average treatment time 12 ± 6 months; 67% dropped the treatment during the 1st year, 27% in the 2nd and 6% during the 3rd year of treatment. Adherence rate determined was 77%. The most frequent reasons for withdrawal were due to economic reasons (47.9%), followed by patients’ perception of no clinical improvement (23%) and change to sublingual immunotherapy (11.6%). Conclusion. Adherence rate in our study was 77%. Economic reasons were the main cause of abandonment in the first year, while the perception of non-improvement was the main reason for abandonment in subsequent years. Adequate information on SCIT prescribing and rigorous monitoring of patients during the treatment can improve adherence.